Camphor alters occipital electrocorticographic patterns during sleep deprivation in Wistar rats - Gurgel do Amaral, Anthony Lucas; Barbosa, Gabriela Brito; Farias dos Santos, Murilo; Vasconcelos de Souza, Luana; Gonçalves dos Santos, Rodrigo; Câmara, Tays Mata; de Sousa Reis, Thaysa; Pacheco Hartcopff, Priscille Fidelis; Eiró-Quirino, Luciana; Araújo da Paz, Clarissa; Bastos de Araújo, Daniella; Favacho Lopes, Dielly Catrina; et al. (Frontiers in Natural Products, 2024)
Introduction Sleep disorders are common in the general population, necessitating the search for new strategies to address this public health challenge. The study aims to describe the electrocorticographic and behavioral changes in sleep deprived Wistar rats exposed to varying doses of camphor, to assess its effects on sleep and its potential as a sleep-inducing drug. Materials and Methods For the electrocorticographic evaluation, seventy-two rats were randomly assigned to distinct groups: a control group, a sleep-deprived group, three sleep-deprived groups receiving 10, 20, and 30 mg/kg i.p. of camphor respectively, and three groups that received these doses without sleep deprivation. For the behavioral analysis, twenty-seven rats were divided into three groups, each receiving the same doses as the previous test. Results and Discussion Our results showed that there was a decrease in the frequency of brain oscillatory patterns when camphor was administered at 10 mg/kg i.p. whereas there was a dose-dependent increase in the spectral power and distribution following the administration of 20 and 30 mg/kg i.p., with the emergence of Delta, Theta, Alpha, and Beta waves. As for the behavioral analysis, it was demonstrated that testicular relaxation, decreased motility, and light sleep induction also occurred in a dose-dependent manner. Thus, we conclude that camphor administration intensifies occipital electrocorticographic patterns in sleep-deprived rats, and its electrocorticographic and behavioral analysis could indicate a potential as a supporting agent in the insomnia treatment.